The Role Of Financial Technology And Customer Behavior Mediation Employee Engagement On Sharia Bank Performance In Padang, West Sumatra Province, Indonesia - Harry Wahyudhi; R. Rozaini; Muhamad Imam Syairozi (Jurnal Scientia, 2024)
This research examined the factors that affect Sharia Bank Performance of the state-owned Islamic banks in Indonesia. Data were collected by distributing an online questionnaire to a total of 250 Muslim customers. Furthermore, the collected data were analyzed using SEMPLS. The findings indicate that Financial Technology (fintech), Customer Behavior (CB) and Employee Engagement (EM) can enhance Sharia Bank Performance (SBP). This suggested that, in Padang West Sumatera Indonesia, where most of the population is Muslim, businesses prioritizing Shariah compliance through Employee Engagement are more likely to retain customers. This research provides empirical evidence to Islamic banks regarding the significance of Employee Engagement. The study suggests that, based on its findings, the various branch managers in charge of EM should develop, nurture, and maintain attractive EM practices as an system to help boost bank performance Based on the findings, bank management tends to consider to integrate the Financial Technology, Customer Behavior and Employee Engagement, into the banking business model.